Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a ) \(x^2\left(x+3\right)+y^2\left(y+5\right)-\left(x+y\right)\left(x^2-xy+y^2\right)=0\)
\(\Leftrightarrow x^3+3x^2+y^3+5y^2-\left(x^3+y^3\right)=0\)
\(\Leftrightarrow3x^2+5y^2=0\)
Do \(\left\{{}\begin{matrix}3x^2\ge0\forall x\\5y^2\ge0\forall y\end{matrix}\right.\)
\(\Rightarrow3x^2+5y^2\ge0\forall x;y\)
Dấu " = " xảy ra
\(\Leftrightarrow\left\{{}\begin{matrix}3x^2=0\\5y^2=0\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}x^2=0\\y^2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\y=0\end{matrix}\right.\)
Vậy \(x=0;y=0\)
b )\(\left(2x-y\right)\left(4x^2+2xy+y^2\right)+\left(2x+y\right)\left(4x^2-2xy+y^2\right)\)
\(-16\left(x^3-y\right)=32\)
\(\Leftrightarrow\left[\left(2x\right)^3-y^3\right]+\left[\left(2x\right)^3+y^3\right]-16x^3+16y=32\)
\(\Leftrightarrow8x^3-y^3+8x^3+y^3-16x^3+16y=32\)
\(\Leftrightarrow16y=32\)
\(\Leftrightarrow y=2\)
Vậy \(y=2\)
a.
=5z(x^2-2x-y^2)
c. =4x^2+6x-2x-3
=(4x^2-2x)+(6x-3)
2x(2x-1)+3(2x-1)
=(2x-1)(2x+3)
a: \(5x^2z-10xyz-5y^2z\)
\(=5z\left(x^2-2xy-y^2\right)\)
b: \(4x^2+4x-3\)
\(=4x^2+6x-2x-3\)
\(=2x\left(2x+3\right)-\left(2x+3\right)\)
\(=\left(2x+3\right)\left(2x-1\right)\)
c: Sửa đề: \(x^2-xy-12y^2\)
\(=x^2-4xy+3xy-12y^2\)
\(=x\left(x-4y\right)+3y\left(x-4y\right)\)
\(=\left(x-4y\right)\left(x+3y\right)\)
d: \(3x+3y-x^2-2xy-y^2\)
\(=3\left(x+y\right)-\left(x+y\right)^2\)
\(=\left(x+y\right)\left(3-x-y\right)\)
\(A=4x^2+y^2+xy+4x+2y+3=4x^2+x\left(y+4\right)+\frac{\left(y+4\right)^2}{16}+y^2-\frac{\left(y+4\right)^2}{16}+2y+3\)\(=\left(2x+\frac{y+4}{4}\right)^2+\frac{16y^2-y^2-8y-16+32y+48}{16}=\left(2x+\frac{y+4}{4}\right)^2+\frac{15y^2+24y+32}{16}\)\(=\left(2x+\frac{y+4}{4}\right)^2+\frac{15\left(y^2+\frac{24}{15}y+\frac{16}{25}\right)+\frac{112}{5}}{16}=\left(2x+\frac{y+4}{4}\right)^2+\frac{15\left(y+\frac{4}{5}\right)^2+\frac{112}{5}}{16}\ge\frac{\frac{112}{5}}{16}=\frac{7}{5}\)Đẳng thức xảy ra khi \(\hept{\begin{cases}2x+\frac{y+4}{4}=0\\y+\frac{4}{5}=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-\frac{2}{5}\\y=-\frac{4}{5}\end{cases}}\)
\(B=-x^2-y^2-2xy=-\left(x+y\right)^2\le0\)
Đẳng thức xảy ra khi x = -y
\(\left(2xy^3+4x^2y^2\right)\div xy\)
\(=xy\left(2y^2+4xy\right):xy\)
\(=2y^2+4xy\)